Exploring EFL learner autonomy in the 2013 Curriculum implementation - Ramadhiyah, Sa'adah; Lengkanawati, Nenden Sri (Universitas Pendidikan Indonesia, 2019)
In the Indonesian educational system, learner autonomy has been demanded to be promoted in the teaching and learning process of recent curriculum implementation. Unfortunately, it cannot be denied that learner autonomy still poses a challenge to be implemented in Indonesia since the teacher-centered learning is still dominant. Therefore, it is essential to explore both teacher’s and students’ perception of learner autonomy in one study. By employing a case study, this study used the interview, observation and questionnaire as the principal data collection methods to see in-depth the teacher’s and students’ perception of learner autonomy. An English teacher and thirty-six students from twelve grade of one senior high school in Indonesia were involved in eliciting their perceptions on learner autonomy and how the teacher’s efforts in promoting learner autonomy in the 2013 Curriculum . The findings showed that the teacher understood the basic features of learner autonomy as learners’ independent learning activity outside the classroom. This study also underlined that the teacher had had the initiative to promote learner autonomy in the 2013 Curriculum implementation by making some efforts. However, the teacher has not yet provided the learning process with a wide variety of authentic materials. It was found that the learners’ attitude toward those three perspectives on learner autonomy did not indicate the students to be autonomous learners because they were still accustomed to the teacher-centered learning environment.